2007
DOI: 10.1158/0008-5472.can-07-0867
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of an Internal Ribosome Entry Site–Dependent Mechanism in Arsenic-Induced GADD45α Expression

Abstract: We have previously shown that trivalent arsenic (arsenite, As 3+ ) is able to induce GADD45A expression in human bronchial epithelial cells through activation of c-Jun NH 2 -terminal kinase and nucleolin-dependent mRNA stabilization. In the present report, we show that As 3+ is capable of inducing translation of the GADD45A protein through a cap-independent, or rather, an internal ribosome entry site (IRES)-dependent mechanism. In growth-arrested cells, As 3+ elevated the GADD45A protein level in a dose-and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 48 publications
(50 reference statements)
1
28
0
Order By: Relevance
“…In addition, GADD45A expression has been recently shown to be regulated through a cap-independent and internal ribosome entry site (IRES)-dependent mechanism in response to cellular stress signals such as arsenic-induced cytotoxic and genotoxic damage (Chang et al 2007). This expression is dependent on an IRES element located in the 5 0 UTR region proximal to the start codon.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GADD45A expression has been recently shown to be regulated through a cap-independent and internal ribosome entry site (IRES)-dependent mechanism in response to cellular stress signals such as arsenic-induced cytotoxic and genotoxic damage (Chang et al 2007). This expression is dependent on an IRES element located in the 5 0 UTR region proximal to the start codon.…”
Section: Discussionmentioning
confidence: 99%
“…tion (18), arsenite (28,47,48,69), and inflammatory cytokines (70). Our previous findings showed that GADD45␣ was one of the crucial mediators of arsenite-induced apoptosis (47,48).…”
mentioning
confidence: 96%
“…The cell growing conditions seem critical for the gadd45␣ mRNA induction by arsenite (69). When the cells were in a logarithmically growing condition, arsenite resulted in a timedependent increase in gadd45␣ mRNA in the late phase of exposure (47,69).…”
mentioning
confidence: 99%
See 2 more Smart Citations